PENGARUH JUMLAH WISATAWAN, PAJAK DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT DI PROVINSI BALI - Devi Sandat Triani, Ni Komang; Bendesa, I. K. G. (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 5, Mei 2018 (pp. 868-1111), 2018)
This research is used to know the number of tourist visit, tax, government to economic growth and prosperity of society in Bali Province. Data settlement method used in this research is non participant observation. The source of this research data comes from secondary data. This study uses analytical techniques. For and the influence of a sobel to analyze influence. Not possible through the intervening variable. Based on the results of this study, the number of indirect and significant tourist visits to the economic growth and welfare of the people in Bali Province. Indirect hotel and restaurant taxes on economic growth and people's prosperity in Bali Province. Direct and significant taxes on the economic growth and prosperity of the people in Bali Province. Indirect economic growth to the welfare of society in Bali Province.   Keywords: number of tourist visit ,  economic growth, public welfare